THE ROLE OF GEO INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE DEVELOPMENT OF YOUTH TOURISM - Axrorova, Nilufar (Центр Научных Публикаций (buxdu.uz), 2023)
The opportunities and reforms for Youth tourism implemented by the government can urge this field to be one of the important markets in the region in a short time. In this case it is essential to do researches and studies successively. This article gives details of functions for mobile apps in order to identify travel destinations of young travellers, form and improve infra and infostructure.